Daya Tarik Budaya Lokal dan Keunikan Objek Wisata: Strategi Media Sosial dalam Meningkatkan Minat Wisatawan ke Aceh Tenggara - Andiansyah, Farma; Gundahara; Dicky Zulkarnaen (Journal Financial, Business and Economics, 2024)
This study analyzes the influence of local culture, uniqueness of tourist attractions, and social media marketing on tourist interest in Southeast Aceh, with social media marketing as a mediating variable. Using quantitative methods with 200 respondents, the results of the study indicate that local culture such as pemamanan culture, pelebat dance, and tasak telu special food have a significant effect on tourist interest. The uniqueness of tourist attractions is also a major factor in attracting tourists, while social media marketing strengthens the relationship between local culture and uniqueness of tourist attractions with tourist interest. This finding is in line with previous studies that emphasize the importance of cultural identity and digital promotion in increasing tourist appeal. The implications of this study underline the need for a local culture-based promotion strategy through social media to increase tourist visits to Southeast Aceh.